2003
DOI: 10.1016/s0736-0266(02)00106-7
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct cellular mechanisms of osteoclast formation and bone resorption in periprosthetic osteolysis

Abstract: Purpose: TNFa and IL-1 a are proinflammatory cytokines that are abundant in periprosthetic tissues. These cytokines stimulate bone resorption and have recently been shown to directly induce osteoclast formation in mouse marrow cultures. We examined whether TNFa and IL-la can directly induce osteoclast formation from human arthroplasty-derived (CD14') macrophages by a mechanism independent of RANKL-induced osteoclastogenesis.Methods; TNFa and M-CSF (HL-la) were added to cultures of magnetically sorted (CD14') a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 61 publications
(49 reference statements)
2
80
0
6
Order By: Relevance
“…Schwarz et al 13 reported that RANK:Fc, a recombinant RANKL antagonist that is formed by fusing the extracellular domain of RANK to the Fc portion of human immunoglobulin G(1), diminished titanium particle-induced osteoclastogenesis and bone resorption in a mouse calvaria model. We demonstrated that an in vivo viralmediated gene transfer of osteoprotegerin (OPG), a secreted TNF receptor-related protein that neutralizes RANKL bioactivity, 6 exerted protective effects against wear debris-induced inflammatory osteolysis. 14 In this study, we utilize the same animal model to demonstrate that EM inhibits wear particle-induced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schwarz et al 13 reported that RANK:Fc, a recombinant RANKL antagonist that is formed by fusing the extracellular domain of RANK to the Fc portion of human immunoglobulin G(1), diminished titanium particle-induced osteoclastogenesis and bone resorption in a mouse calvaria model. We demonstrated that an in vivo viralmediated gene transfer of osteoprotegerin (OPG), a secreted TNF receptor-related protein that neutralizes RANKL bioactivity, 6 exerted protective effects against wear debris-induced inflammatory osteolysis. 14 In this study, we utilize the same animal model to demonstrate that EM inhibits wear particle-induced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] RANKL, a membrane-bound factor expressed on the surface of stromal cells/ osteoblasts, 7 stimulates osteoclastogenesis by signaling through its membrane receptor RANK. 7,8 Both the expression and activity of RANK/RANKL mediators is, in turn, regulated by many factors, such as TNF-a and IL-1b, that have been shown to be present in the tissue adjacent to loose implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue has a high synthetic activity 1 and may contribute to bone lysis, which was first described in 1977. 2 Wear particles 3,4 trigger the invasion of inflammatory cells into the interface tissue. Some cell populations of the interface tissue release matrix-degrading enzymes 5 and cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, there is controversy as to whether TNFa can stimulate myeloid osteoclastogenesis by a RANK/RANKL independent mechanism. 11,12 Sabokbar et al 13 found that the addition of TNFa to macrophages isolated from human loosening periprosthetic tissues induced the formation of TRAP þ multinucleated osteoclasts capable of extensive lacunar resorption. TNFa-induced osteoclastogenesis cannot be blocked by the treatment with either osteoprotegerin (OPG) or RANK:Fc IgG (which inhibit RANKL-induced osteoclastogenesis), suggesting this process is distinct from the RANK/RANKL signaling pathway.…”
Section: Introductionmentioning
confidence: 99%